Empowering the Young Generation of Indonesia through Shariah Investments - Iman Maulana, Nurul (Sharia Business Management Department of STEBIS Bina Mandiri, 2025)
Shariah investment presents a powerful tool for empowering Indonesia's younger generation and promoting sustainable economic growth. This study highlights the role of Shariah-compliant investments in fostering an inclusive financial system that aligns with Islamic ethical principles. By integrating the prohibition of interest (riba), excessive speculation (gharar), and investment in unethical industries, Shariah investments encourage fairness and social responsibility in economic activities. The research emphasizes that beyond financial returns, these investments serve as vehicles for social justice, ethical finance, and equitable wealth distribution. Shariah investments also empower young individuals by offering a means to align their financial activities with their moral and religious values. With appropriate regulatory support and market growth, Shariah investment holds the potential to drive long-term prosperity and social cohesion, particularly in developing economies like Indonesia.